Nitrogen and Biochar Addition Affected Plant Traits and Nitrous Oxide Emission From Cinnamomum camphora - Zhu, Congfei; Luo, Handong; Luo, Laicong; Wang, Kunying; Liao, Yi; Zhang, Shun; Huang, Shenshen; Guo, Xiaomin; Zhang, Ling (Frontiers in Plant Science, 2022)
Atmospheric nitrous oxide (N2O) increase contributes substantially to global climate change due to its large global warmig potential. Soil N2O emissions have been widely studied, but plants have so far been ignored, even though they are known as an important source of N2O. The specific objectives of this study are to 1) reveal the effects of nitrogen and biochar addition on plant functional traits and N2O emission of Cinnamomum camphora seedlings; 2) find out the possible leaf traits affecting plant N2O emission. The effects of nitrogen and biochar on plant functional traits and N2O emissions from plants using C. camphora seedlings were investigated. Plant N2O emission, growth, each organ biomass, each organ nutrient allocation, gas exchange parameters, and chlorophyll fluorescence parameters of C. camphora seedlings were measured. Further investigation of the relationships between plant N2O emission and leaf traits was performed by simple linear regression analysis, principal component analysis (PCA), and structural equation model (SEM). It was found that nitrogen addition profoundly increased cumulative plant N2O emissions (+109.25%), which contributed substantially to the atmosphere's N2O budget in forest ecosystems. Plant N2O emissions had a strong correlation to leaf traits (leaf TN, Pn, Gs, Ci, Tr, WUEL, α, ETRmax, Ik, Fv/Fm, Y(II) and SPAD). Structural equation modelling revealed that leaf TN, leaf TP, Pn, Ci, Tr, WUEL, α, ETRmax and Ik were key traits regulating the effects of plants on N2O emission. These results provide a direction for understanding the mechanism of N2O emission from plants and provide a theoretical basis for formulating corresponding emission reduction schemes.